The effect of Cr concentration and preparation method on the microstructure and electrical characterization of SnO2-based ceramics - Leite, Daniela Russo [UNESP]; Las, Wanda Cecilia [UNESP]; Zaghete, Maria Aparecida [UNESP]; Cilense, Mario [UNESP]; Varela, Jose Arana [UNESP] (ABM, ABC, ABPol, 2003)
This paper reports a study of the influence of Cr concentration and preparation method in the electrical conductivity and microstructure of SnO2-based powders doped with Mn and Nb, prepared by an organic route (Pechini method) and a mixture of oxides. All the samples were compacted into discs and sintered at 1300 °C for 3h, resulting in ceramics with relative density varying between 81 and 99%. The powders were morphologically characterized by X-ray diffraction and their specific surface area was determined by N2 adsorption/desorption isotherms. Electrical conductivity characterization indicated that the conductivity decreases as Cr concentration increases, probably due to Cr segregation at grain boundaries, which reduces grain size, increasing the number of resistive boundaries, thus limiting the passage of current.
Keywords: SnO2; conductivity; chromium